Investigation on the use of cold formed perforated steel sections as columns and purlins - V.V, Athira; S, Sruthy (International Journal of Engineering and Technology, 2018)
Perforations are required in columns and purlins of a trussed building for making connections, for fixing electrical fixtures etc. An inves- tigation was undertaken to study the effect of perforations in cold-formed C and Z sections used as columns and purlins. For this purpose, finite element model was developed using ANSYS software. Six different shapes of perforations were considered to investigate the shape that gives maximum buckling load. The perforation pattern which is optimum for the individual section was applied to frames and then to the building and optimum type of perforation is suggested. Buckling loads of frames and building with and without perforation was done separately and results were compared. By considering perforations with equal area, linear buckling analysis was done and stress pattern around perforation was studied. Even though the area reduction was equal, differently shaped perforations gave different buckling load. In this case, stress concentration has an important role; buckling load is higher for the shape with least stress concentration.Â Â Â